The History and Philosophy of Science as a subsidy for a didactic strategy on radioactivity (Research, Society and Development, 2019)
This work aims to report a didactic sequence for the theme of radioactivity through the History of Science. The strategies used were conversation wheel, analysis of texts, experimentation and debates. The intervention seeks to address the studies involving radioactivity and the historical context of the period between Henri Becquerel and Marie Curie. The main objective is to show students that science is not ready because it is built collectively. The questions answered by the students point to a better understanding of the scientist's work, not considering it socially neutral and random to the world. The results showed that scientific knowledge was assimilated gradually and that the methods used have led to a dialogue of knowledge.